Mold release film, film laminate, and method for producing film and film laminate

By unevenly distributing fluorine atoms on the surface of the release film and combining curable silicone materials and catalysts, the problem of strong adhesion of fluorine silicone materials is solved, and the light peelability and durability are improved, reducing the cost of use.

JP2025020246AActive Publication Date: 2025-02-12MITSUBISHI CHEM CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024190466
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-07-29
Filing Date
2024-10-30
Publication Date
2025-02-12
Estimated Expiration
2040-04-14

AI Technical Summary

Technical Problem

In the prior art, the release film using a fluorine-containing silicone material has a problem of strong adhesiveness and difficulty in peeling when separated from the silicone adhesive. At the same time, the fluorine-silicone material is expensive and difficult to recycle, resulting in a reduced usage requirement and insufficient durability.

Method used

By distributing fluorine atoms unevenly on the surface of the release film, XPS measurement is performed using the gas cluster ion beam GC-IB technology to control the concentration distribution of fluorine atoms in the release layer, so that they are at a high concentration on the surface, and the use of curable silicone materials and catalysts is combined to form a release layer with light peelability and durability.

Benefits of technology

While reducing the use of fluorosilicone, it is achieved to improve the light peelability and durability of the release film, reduce production costs and improve the use efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025020246000001_ABST
    Figure 2025020246000001_ABST
Patent Text Reader

Abstract

To provide a novel release film that has an excellent light-level releasing property and is easy to peel off from a silicone adhesive layer, and can reduce an amount of fluorinated silicone used, and a film laminate using the release film.SOLUTION: There is provided a mold release film having a mold release layer formed by curing a mold release layer composition containing: a (A) curable silicone having a fluorine substituent; a (B) curable silicone having no fluorine substituent; and a (D) curing catalyst, on at least one surface side of a substrate film, wherein in a concentration distribution of fluorine atoms in a thickness direction within the mold release layer, fluorine atoms are unevenly distributed on a surface of the mold release layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a release film, a film laminate using the same, a method for producing the same, and a method for using the same. [Background technology]

[0002] In recent years, the number of automobiles equipped with liquid crystal panels has been increasing. In-vehicle applications such as these are often exposed to high and low temperatures for long periods of time, so the adhesive used to bond the panel components is also required to have high weather resistance and heat resistance. Silicone adhesives, which are primarily made of silicone, are attracting attention as an adhesive that meets this requirement.

[0003] Silicone adhesives have excellent heat resistance, chemical resistance, and transparency, and are characterized by their ability to adhere to materials that are difficult to adhere to with general adhesives, such as silicone rubber, fluororesin, and metals, as well as excellent re-adhesiveness. Silicone adhesives are used in the form of tapes (films) with the adhesive layer as the adhesive. Before use, they are usually stored with one or both sides covered with a release film, and when in use, the release film is peeled off.

[0004] As the release film used for this type of application, a silicone release film which is obtained by coating a base film with a silicone release agent is widely used. However, when such a silicone release film is coated with a silicone adhesive, the adhesive and the release film tend to adhere strongly to each other, making them difficult to peel off, because the chemical structures of the release agent and the adhesive are similar. Therefore, in order to reduce the peel strength of the silicone adhesive (to make it easier to release), fluorine has been introduced into the silicone release agent. For example, Patent Document 1 proposes a fluorinated silicone material having a fluorine substituent to exhibit release properties against the silicone adhesive. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2011-201035 A Summary of the Invention [Problem to be solved by the invention]

[0006] Silicones having fluorine substituents (also called "fluorinated silicones") as disclosed in Patent Document 1 are substances with high chemical stability and low toxicity. However, fluorinated silicones are expensive, and therefore there is a demand for reducing the amount of fluorinated silicones used. In addition, release films coated with fluorinated silicone release agents are difficult to recycle, and therefore there is a demand for reducing the amount of fluorinated silicones used from this point of view as well. In addition, the durability of the release layer has sometimes been an issue.

[0007] Therefore, the present invention aims to provide a new silicone release film formed using fluorinated silicone, which has light releasability from a silicone pressure-sensitive adhesive layer and can reduce the amount of fluorinated silicone used, and a film laminate using the release film.The present invention also aims to provide a new release film that can increase the durability of the release layer, and a film laminate using the release film. [Means for solving the problem]

[0008] The present invention proposes a first release film having a release layer formed by curing a release layer composition containing (A) a curable silicone having a fluorine substituent, (B) a curable silicone not containing a fluorine substituent, and (D) a curing catalyst on at least one side of a base film, wherein the release film is characterized in that, in the fluorine atom concentration distribution in the thickness direction within the release layer, fluorine atoms are unevenly distributed on the surface of the release layer, and the fluorine atom concentration on the surface of the release layer is 39.0 atomic concentration % or more.

[0009] The present invention also relates to a second release film having a release layer formed by curing a release layer composition containing (A) a curable silicone having a fluorine substituent, (B) a curable silicone not containing a fluorine substituent, and (D) a curing catalyst on at least one side of a base film, the second release film being characterized in that the fluorine atom concentration distribution in the thickness direction of the release layer is measured at a constant sputtering rate using XPS (X-ray photoelectron spectroscopy) with GC-IB (gas cluster ion beam), and the resulting fluorine atom concentration distribution (vertical axis: fluorine atom concentration (atom%), horizontal axis: sputtering time (min)) is divided equally into nine by the total sputtering time to determine a first measurement point (sputtering time 0), a second measurement point, a tenth measurement point, We propose a release film characterized in that the fluorine atomic concentration (atom%) at the second to tenth measurement points is 80.0% or less of the fluorine atomic concentration (atom%) at the first measurement point (sputtering time 0), that is, 80.0% or less when the fluorine atomic concentration (atom%) at the first measurement point (sputtering time 0) is set to 100.0%.

[0010] The present invention also relates to a third release film having a release layer formed by curing a release layer composition containing (A) a curable silicone having a fluorine substituent, (B) a curable silicone not containing a fluorine substituent, and (D) a curing catalyst on at least one side of a base film, the third release film being characterized in that the release layer is formed by curing a release layer composition containing (A) a curable silicone having a fluorine substituent, (B) a curable silicone having no fluorine substituent, and (D) a curing catalyst, the third release film being characterized in that the release layer is formed by measuring the concentration distribution of fluorine atoms in the thickness direction in the release layer at a constant sputtering rate using XPS (X-ray photoelectron spectroscopy) and GC-IB (gas cluster ion beam), and the resulting fluorine atom concentration distribution (vertical axis: fluorine atom concentration (atom%), horizontal axis: sputtering time (min)) is divided equally into nine by the total sputtering time to determine a first measurement point (sputtering time 0), a second measurement point, a tenth measurement point, We propose a release film characterized in that the average fluorine atomic concentration (atom%) at the 6th to 10th measurement points is higher than 2.2% of the fluorine atomic concentration (atom%) at the first measurement point (sputtering time 0), that is, higher than 2.2% when the fluorine atomic concentration (atom%) at the first measurement point (sputtering time 0) is set to 100.0%.

[0011] The present invention also proposes a method for producing a release film, which comprises mixing (A) a curable silicone having a fluorine substituent, (C) a silicone crosslinking agent, and (D) a curing catalyst, stirring and / or allowing to stand (in the present invention, this treatment is also referred to as "pretreatment"), and then mixing the mixture with (B) a curable silicone having no fluorine substituent to prepare a release layer composition, and applying this release layer composition to at least one side of a substrate film. Effect of the Invention

[0012] The first and second release films proposed by the present invention relate to a release layer formed using fluorinated silicone, and in the concentration distribution of fluorine atoms in the thickness direction of the release layer, fluorine is unevenly distributed on the surface of the release layer, thereby providing easy peelability from the silicone adhesive layer while still allowing the amount of fluorinated silicone used to be reduced. In addition, the third release film proposed by the present invention relates to a release layer formed using fluorinated silicone, and by making fluorine present inside the release layer, the durability of the release layer can be improved. Moreover, according to the method for producing a release film proposed in the present invention, such a release film can be suitably produced. [Brief description of the drawings]

[0013] [Figure 1] 1 is a graph showing the atomic concentration distribution of carbon (C), oxygen (O), silicon (Si), and fluorine (F) (vertical axis: each atomic concentration (atom%), horizontal axis: sputtering time (min)) as measurement data of XPS (X-ray photoelectron spectroscopy) obtained in Example 1. [Diagram 2] 1 is a graph showing the atomic concentration distribution of carbon (C), oxygen (O), silicon (Si), and fluorine (F) (vertical axis: each atomic concentration (atom%), horizontal axis: sputtering time (min)) as measurement data of XPS (X-ray photoelectron spectroscopy) obtained in Example 2. [Diagram 3]FIG. 13 is a graph showing the atomic concentration distributions of carbon (C), oxygen (O), silicon (Si) and fluorine (F) (vertical axis: each atomic concentration (atom%), horizontal axis: sputtering time (min)) as measurement data of XPS (X-ray photoelectron spectroscopy) obtained in Example 5. [Figure 4] 1 is a graph showing the atomic concentration distribution of carbon (C), oxygen (O), silicon (Si), and fluorine (F) (vertical axis: each atomic concentration (atom%), horizontal axis: sputtering time (min)) as measurement data of XPS (X-ray photoelectron spectroscopy) obtained in Comparative Example 1. [Diagram 5] 1 is a graph showing the atomic concentration distribution of carbon (C), oxygen (O), silicon (Si), and fluorine (F) (vertical axis: each atomic concentration (atom%), horizontal axis: sputtering time (min)) as measurement data of XPS (X-ray photoelectron spectroscopy) obtained in Comparative Example 2. [Figure 6] 1 is a graph showing the atomic concentration distribution of carbon (C), oxygen (O), silicon (Si), and fluorine (F) (vertical axis: each atomic concentration (atom%), horizontal axis: sputtering time (min)) as measurement data of XPS (X-ray photoelectron spectroscopy) obtained in Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Next, the present invention will be described based on an embodiment, however, the present invention is not limited to the embodiment described below.

[0015] <<Release film>> A release film according to one embodiment of the present invention (referred to as "this release film") has a release layer (referred to as "this release layer") on one or both sides of a base film (referred to as "this base film"), the release layer being formed by curing a release layer composition (referred to as "this release layer composition") containing (A) a curable silicone having a fluorine substituent (also referred to as "fluorinated curable silicone"), (B) a curable silicone not containing a fluorine substituent (also referred to as "non-fluorinated curable silicone"), and (D) a curing catalyst, and optionally further containing (C) a silicone crosslinking agent.

[0016] <Main release layer> The present release layer is a layer formed by curing the present release layer composition, and in the concentration distribution of fluorine atoms in the thickness direction of the release layer, fluorine is preferably unevenly distributed on the surface of the release layer. By unevenly distributing fluorine on the surface of the release layer in this manner, excellent easy releasability can be achieved that allows easy peeling from the silicone pressure-sensitive adhesive layer, and the amount of fluorinated silicone used can be reduced.

[0017] The release layer is measured for the concentration distribution (ratio) of fluorine (F) atoms in the thickness direction of the release layer at a constant sputtering rate using XPS (X-ray photoelectron spectroscopy) with GC-IB (gas cluster ion beam), and the obtained fluorine atom concentration distribution (vertical axis: fluorine atom concentration (atom%), horizontal axis: sputtering time (min)) is divided equally into 9 parts by the total sputtering time to determine the first measurement point (sputtering time 0), the second measurement point, to the tenth measurement point. At the first measurement point (sputtering time 0), that is, the fluorine atom concentration (atom%, also referred to as atomic concentration%) on the release layer surface is 39.0% or more, preferably 39.5% or more, and more preferably 40.0% or more. On the other hand, the upper limit is not limited, but is generally 60.0% or less, and more preferably 50.0% or less.

[0018] In addition, the fluorine atom concentration (atom%) of the release layer at the second to tenth measurement points is preferably 80.0% or less, more preferably 70.0% or less, even more preferably 60.0% or less, even more preferably 40.0% or less, and even more preferably 30% or less, when the fluorine atom concentration (atom%) at the first measurement point (sputtering time 0) is taken as 100.0%. There is no particular restriction on the lower limit. However, it is generally higher than 2.2%, and is preferably 3.0% or more, even more preferably 4.0% or more, and even more preferably 5.0% or more. Here, since the sputtering time correlates with the depth from the surface of the release layer, the sputtering time can be read as an index of the depth from the surface of the release layer.

[0019] In order to make fluorine unevenly distributed on the surface of the release layer as described above, it is preferable to prepare the release layer composition by carrying out a "pre-treatment" as described below, for example. However, the method is not limited to this.

[0020] Furthermore, when the fluorine atom concentration (atom%) at the first measurement point (sputtering time 0) is taken as 100.0%, the average fluorine atom concentration (atom%) at the sixth to tenth measurement points is preferably higher than 2.2%, and more preferably 3.0% or more, more preferably 4.0% or more, and even more preferably 5.0% or more. However, taking into consideration the viewpoint of distributing fluorine more unevenly on the release layer surface, it is preferably 30.0% or less, more preferably 20.0% or less, and even more preferably 10.0% or less. By carrying out the "pre-treatment" described below, more fluorine is distributed inside the release layer (closer to the substrate) compared to when the pre-reaction was not carried out. Although the detailed mechanism is not clear, it is speculated that fluorine is distributed from intermediates (fluorinated silicone resins with one or more crosslinking agents bonded to them, but the crosslinking reaction between the fluorinated silicone resins has not yet occurred) that are reaction products of the "pre-treatment" and from by-products. In order to make fluorine unevenly distributed on the surface of the release layer and to have a certain amount of fluorine contained in the inside of the release layer, it is preferable to carry out the "pre-treatment" described later more thoroughly, although the present invention is not limited to such a method.

[0021] As described above, since the sputtering time correlates with the depth from the surface of the release layer, the above ratios may be obtained using the depth from the surface of the release layer instead of the sputtering time. In this case, when the measurement of the fluorine atom concentration (atom%) is performed, if the distance from the surface of the release layer to the underlayer, i.e., the base film, does not exactly become 9 sections due to film thickness fluctuations during the preparation of the measurement sample, the fluorine atom concentrations (atom%) at the first to tenth measurement points may be calculated by dividing the distance into 9 sections using another parameter.

[0022] The fluorine atom content in this release layer is preferably 500 mass ppm or more, more preferably 1000 mass ppm or more, more preferably 3000 mass ppm or more, from the viewpoint of obtaining stable and favorable easy peeling property for silicone adhesive.On the other hand, from the viewpoint of reducing the amount of fluorinated silicone used to reduce the fluorine atom content, it is preferably 800000 mass ppm or less, more preferably 700000 mass ppm or less, more preferably 500000 mass ppm or less, more preferably 300000 mass ppm or less.

[0023] <This release layer composition> The release layer composition comprises (A) a curable silicone having a fluorine substituent, (B) a curable silicone having no fluorine substituent, and (D) a curing catalyst, and optionally further comprises (C) a silicone crosslinking agent.

[0024] ((A) Curable silicone having a fluorine substituent) A curable silicone having a fluorine substituent can impart stable and easy releasability to a silicone pressure sensitive adhesive. Silicone is a polymer whose backbone is a siloxane bond (≡Si-O-Si≡) consisting of silicon and oxygen, with organic groups mainly composed of methyl (-CH3) bonded to the silicon (Si). "Curable silicone" is silicone that can be cured through a crosslinking reaction by heating or exposure to light (ultraviolet rays).

[0025] The term "fluorine substituent" refers to a substituent containing a fluorine atom. The substituent containing a fluorine atom (fluorine substituent) is not particularly limited as long as the substituent contains a fluorine atom. Specific examples include a fluorine group, a trifluoromethyl group, a pentafluoroethyl group, a 2,2-trifluoroethyl group, a 1H,1H-heptafluorobutyl group, a 2H-hexafluoroisopropyl group, a perfluoro-t-butyl group, and a perfluorohexyl group. However, the examples are not limited to these. Furthermore, examples of components having a fluorine substituent include resins that contain a fluorine substituent in the side chain portion of the resin skeleton.

[0026] Specific examples of the curable silicone having a fluorine substituent include KP-911, X-70-201S, and X-41-3035 manufactured by Shin-Etsu Chemical Co., Ltd., and FS1265-300CS, FS1265-1000CS, FS1265-10000CS, BY24-900, BY24-903, 3062, Q2-7785, SYL-OFF 7792, and SYL-OFF 7795 manufactured by Dow Corning Toray Co., Ltd. However, the examples are not limited to these.

[0027] The curable silicone having a fluorine substituent may be of the solvent type, of the solventless type, or of a mixture of these. The fluorine-substituted curable silicones may be used alone or in combination of two or more kinds.

[0028] Here, "solventless curing silicone" refers to a silicone with a viscosity that allows it to be applied without diluting it with a solvent, and is made up of short polysiloxane chains and has a relatively low molecular weight. The viscosity of the solventless curable silicone alone is preferably 1000 mPa·s or less, more preferably 50 mPa·s or more or 900 mPa·s or less, and even more preferably 80 mPa·s or more or 800 mPa·s or less. This also applies to (B) curable silicones that do not contain fluorine substituents.

[0029] On the other hand, "solvent-curable silicone" is a silicone that has such a high viscosity that it cannot be applied unless it is diluted with a solvent, and is a silicone with a relatively high molecular weight. This also applies to "(B) Curable silicone that does not contain fluorine substituents." The viscosity of the solvent-curable silicone is preferably 1000 mPa·s or more when made into a 30% toluene solution, more preferably 2000 mPa·s or more or 20000 mPa·s or less, and even more preferably 3000 mPa·s or more or 18000 mPa·s or less. When the solvent-curable silicone has a high viscosity, it tends to have high adhesion to the substrate film. This also applies to (B) curable silicone that does not contain a fluorine substituent.

[0030] The fluorine atom content (atomic fraction) of a curable silicone having a fluorine substituent is generally on the order of several thousand ppm (less than 1% of the total number of atoms in the "curable silicone having a fluorine substituent") to several hundred thousand ppm (several tens of% of the total number of atoms in the "curable silicone having a fluorine substituent").

[0031] ((B) Curable silicone containing no fluorine substituents) The curable silicone not containing a fluorine substituent may be a solvent-based or solventless type, or a mixture of these. Among these, from the viewpoint of obtaining stable easy release properties for silicone pressure sensitive adhesives, (B) the curable silicone not containing a fluorine substituent is preferably a solvent-based curable silicone.

[0032] Specific examples of curable silicones not containing fluorine substituents include KNS-3051, KNS-320A, KNS-316, KNS-3002, KNS-3300, X-62-1387, KS-837, X-62-2829, KS-3650, KS-847, KS-847T, KS-776L, KS-776A, KS-774, KS-3703T, KS-3601, KS-830E, X-62-2825, X-62-9201-A, X-62-9201B, KM3951, KM-768, X-52-6015, KF-2005, and X-62-7205 manufactured by Shin-Etsu Chemical Co., Ltd. , X-62-7028-A, X-62-7028-B, X-62-7052, X-62-7622, ​​X-62-7660, and X-62-7655; SP7017, SP7015, SP7025, SP7031, LTC1006L, LTC1063L, LTC1036M, LTC1056L, SRX357, SRX211, SRX345, SRX370, LTC300B, LTC310, LTC355A, LTC759, LTC755, LTC750A, LTC752, LTC761, LTC856, and LTC851 manufactured by Dow Corning Toray Co., Ltd., but are not limited thereto.

[0033] Further, a high release additive may be added to the non-fluorinated curable silicone. Examples of such additives include KS-3800 manufactured by Shin-Etsu Chemical Co., Ltd.; SD7292 and BY24-4980 manufactured by Dow Corning Toray Co., Ltd.

[0034] The non-fluorinated curable silicone may be used alone, or two or more types having different reactive functional groups or different viscosities may be mixed and used. By mixing two or more kinds of non-fluorinated curable silicones, it is possible to adjust the curing reaction, adjust the viscosity of the coating liquid, and further increase the wettability and reactivity. In this case, it is possible to mix solventless silicones together, mix solvent-type silicones together, or mix solventless silicone and solvent-type silicone. In particular, when the film thickness is increased to obtain a release film with lighter peeling properties, the solid content concentration of the coating liquid forming the cured layer tends to be high. Therefore, there is a possibility that the viscosity of the coating liquid increases, causing problems such as deterioration of the coat appearance and large thickness unevenness. Therefore, by mixing solventless silicones and solvent-type silicones, it is possible to reduce the viscosity of the coating liquid and form a cured layer with good coat appearance and small thickness fluctuation. The solvent-curable silicone and the solventless-curable silicone are as described above, and the preferred viscosity ranges of each are also the same as those described above.

[0035] (Ratio of (A) to (B)) In the present release layer composition, the mass ratio of (A) the curable silicone having a fluorine substituent to (B) the curable silicone not having a fluorine substituent is preferably 1:50 to 10:1, more preferably 1:20 to 5:1, even more preferably 1:10 to 2:1, and even more preferably 1:5 to 1:1.

[0036] As explained above, in the present invention, it is preferable to use a curable silicone that cures via a hydrosilylation addition reaction, particularly "(A) a curable silicone having a fluorine substituent", from the standpoint of material availability. On the other hand, in producing "a release film characterized in that, in the concentration distribution of fluorine atoms in the thickness direction of the release layer, the fluorine atom concentration is higher on the surface of the release layer than in the interior of the release layer," which is a feature of the present invention, there are no particular limitations on the curing method, and curing silicones such as condensation type and UV curing type may be used.

[0037] ((C) Silicone Crosslinker) A "crosslinker" is a compound that links polymers together, for example a compound that can link two or more molecules together by a covalent chemical bond.

[0038] Examples of silicone crosslinkers include (C1) silicone crosslinkers that do not contain fluorine substituents (also referred to as "non-fluorinated silicone crosslinkers") and (C2) silicone crosslinkers that contain fluorine substituents (also referred to as "non-fluorinated silicone crosslinkers"). Among these, it is preferable to use a non-fluorinated silicone crosslinking agent (C1) from the viewpoint of ensuring the effect of the pre-reaction described below, increasing the uneven distribution of fluorine, i.e., increasing the easy peelability, and increasing the residual adhesion rate. When using a mixture of both, it is preferable to use a larger amount of (C1).

[0039] ((C1) Silicone crosslinker containing no fluorine substituents) The "(C1) silicone crosslinking agent containing no fluorine substituents" is represented by the following general formula (1), and has at least two, preferably three or more (usually about 3 to 200), more preferably 3 to 100, and particularly preferably 3 to 50 silicon-bonded hydrogen atoms (SiH groups) in one molecule.

[0040] R b H c SiO (4-b-c) / 2 (1)

[0041] In formula (1), R is an unsubstituted or substituted monovalent hydrocarbon group having 1 to 10 carbon atoms, b is 0.7 to 2.1, particularly 0.8 to 2.0, c is 0.001 to 1.0, and b+c is a positive number that satisfies 0.8 to 3.0, particularly 1.0 to 2.5.

[0042] Here, examples of R include the same groups as R in the alkenyl group-containing organopolysiloxane, but it is preferable that the R does not have an aliphatic unsaturated bond such as an alkenyl group.

[0043] The silicon-bonded hydrogen atoms may be bonded to silicon atoms at the ends of the molecular chain, or to silicon atoms in the middle of the molecular chain (non-terminal), or to both.

[0044] The molecular structure of the "(C1) silicone crosslinking agent containing no fluorine substituents" may be any of linear, cyclic, branched, and three-dimensional network structures. Furthermore, the number of silicon atoms in one molecule (or the degree of polymerization) is preferably 2 to 1,000, more preferably 3 or more or 500 or less, even more preferably 3 or more or 300 or less, and even more preferably 4 or more or 150 or less.

[0045] Examples of "(C1) silicone crosslinking agents not containing fluorine substituents" include tris(dimethylhydrogensiloxy)methylsilane, tris(dimethylhydrogensiloxy)phenylsilane, 1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane, methylhydrogencyclopolysiloxane, methylhydrogensiloxane-dimethylsiloxane cyclic copolymer, methylhydrogenpolysiloxane capped at both ends with trimethylsiloxy groups, dimethylsiloxane-methylhydrogen capped at both ends with trimethylsiloxy groups, copolymer of dimethylsiloxane, dimethylpolysiloxane capped at both ends with dimethylhydrogensiloxy groups, methylhydrogenpolysiloxane capped at both ends with dimethylhydrogensiloxy groups, copolymer of dimethylsiloxane and methylhydrogensiloxane capped at both ends with dimethylhydrogensiloxy groups, copolymer of methylhydrogensiloxane and diphenylsiloxane capped at both ends with trimethylsiloxy groups, copolymer of methylhydrogensiloxane, diphenylsiloxane and dimethylsiloxane capped at both ends with trimethylsiloxy groups, (CH3)2HSiO 1 / 2 Units and SiO 4 / 2 A copolymer consisting of (CH3)2HSiO units. 1 / 2 Units and SiO 4 / 2 Units and (C6H5)SiO 3 / 2and copolymers consisting of these exemplified compounds in which some or all of the methyl groups have been substituted with other alkyl groups such as ethyl groups and propyl groups, or aryl groups such as phenyl groups, but are not limited thereto. It is preferable to use two or more types of crosslinking agents in combination. The combined use is also intended to promote the crosslinking reaction.

[0046] The content of "(C1) silicone crosslinking agent not containing a fluorine substituent" (the total amount when multiple types are used) is preferably 0.1 to 50 parts by mass relative to 100 parts by mass of the curable silicone ((A) + (B)), and more preferably 0.3 parts by mass or more or 30 parts by mass or less, and even more preferably 0.5 parts by mass or more or 20 parts by mass or less.

[0047] The molar ratio of silicon-bonded hydrogen atoms (SiH groups) in the silicone crosslinking agent (C) to the combined total of silicon-bonded alkenyl groups in the curable silicone having fluorine substituents (A) and silicon-bonded alkenyl groups in the curable silicone not containing fluorine substituents (B) is preferably 0.3 to 3.0, and is more preferably 0.5 or more or 2.5 or less, and even more preferably 0.8 or more or 2.0 or less.

[0048] Specific examples of the "(C1) silicone crosslinking agent not containing a fluorine substituent" include 3062A, 3062B, 3062D, and SP 7297 manufactured by Dow Corning Toray Co., Ltd.

[0049] ((C2) Silicone Crosslinker Containing Fluorine Substituents) On the other hand, (C2) a silicone crosslinking agent containing a fluorine substituent can be exemplified by the above formula (1) in which R has a fluoro group. Specific examples include 3062C and Q2-7560 manufactured by Dow Corning Toray Co., Ltd.

[0050] ((D) Curing catalyst) The "curing catalyst" is a catalyst for promoting the hydrosilylation addition reaction between an alkenyl group bonded to a silicon atom of a curable silicone and a hydrogen silane (SiH) group of the silicone crosslinking agent (C). Examples of the curing catalyst include platinum-based catalysts such as platinum black, platinic chloride, chloroplatinic acid, a reaction product of chloroplatinic acid with a monohydric alcohol, a complex of chloroplatinic acid with an olefin, platinum group metal catalysts such as platinum bisacetoacetate, palladium catalysts, and rhodium catalysts, but are not limited to these.

[0051] The content of the curing catalyst in the present release layer composition or in the present release layer is preferably 0.5 to 500 ppm by mass, calculated as the metal amount, relative to the total amount of the curable silicone ((A) + (B)), and more preferably 5 ppm by mass or more or 500 ppm by mass or less, and even more preferably 10 ppm by mass or more or 200 ppm by mass or less.

[0052] ((E) Reaction control agent) The present release layer composition and the present release layer may contain a reaction inhibitor in addition to the above components, if necessary.

[0053] As the (E) reaction inhibitor, acetylene alcohol represented by the following general formula (2) can be used.

[0054] CH≡CC(R2)(OH)R1(2)

[0055] In formula (2), R1 is a linear or branched monovalent hydrocarbon group having 5 to 15 carbon atoms, and R2 is a linear monovalent hydrocarbon group having 1 to 3 carbon atoms.

[0056] In the above formula (2), R1 is preferably a linear or branched monovalent hydrocarbon group having 5 to 15 carbon atoms, more preferably 6 to 14 carbon atoms, and particularly preferably 8 to 12 carbon atoms. Specific examples of R1 include alkyl groups such as pentyl, neopentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, and dodecyl, and alkenyl groups such as pentenyl, hexenyl, and heptenyl, but are not limited to these. In the above formula (2), if the carbon number of the monovalent hydrocarbon group of R1 is less than 5, the control agent may be highly volatile and the control effect may be insufficient. On the other hand, if the carbon number is more than 15, the amount of active ingredient of acetylene alcohol per mole decreases and the control effect tends to be weak, so there is a concern that a large amount must be added to obtain the desired control effect.

[0057] In the above formula (2), R2 is a linear monovalent hydrocarbon group having 1 to 3 carbon atoms, preferably 1 to 2. Specific examples of R2 include alkyl groups such as methyl, ethyl, and n-propyl groups, and alkenyl groups such as vinyl, allyl, and n-propenyl groups. However, the examples are not limited to these. The fewer the carbon atoms in R2, the easier it is to achieve the control effect of the silicone composition, and a methyl group is preferable.

[0058] The reaction inhibitor may be used alone or in combination of two or more kinds, if necessary. The content of the reaction inhibitor is preferably 0.001 to 5.0 parts by mass per 100 parts by mass of the total amount of the release layer composition, and more preferably 0.01 part by mass or more or 1.0 part by mass or less, and even more preferably 0.05 part by mass or more or 0.5 part by mass or less.

[0059] (Other Ingredients) The release layer composition and the release layer may contain other components as necessary, in addition to the above components. For example, silicones other than curable silicones, silicone rubbers, silicone resins, polyolefin resins, acrylic resins, urethane resins, epoxy resins, alkyd resins, cellulose resins, and other resins, and copolymers of these resins modified by graft polymerization, etc.; various particles such as silica particles, alumina particles, silicone rubber particles, silicone resin particles, and silicone rubber / resin composite particles; silane coupling agents, etc. can be mentioned. However, they are not limited to these.

[0060] The present release layer composition and the present release layer may contain, for example, a light releasing agent, a heavy releasing agent, a crosslinking agent, and an adhesion improving agent, as necessary. Specific examples of the light release agent, heavy release agent, and adhesion improver include KS-3800 and X-92-185 manufactured by Shin-Etsu Chemical Co., Ltd., and BY24-850, SD7292, BY24-4980, SP7297, BY24-808, and SD7200 manufactured by Dow Corning Toray Co., Ltd., but are not limited to these.

[0061] (Solids) The solids concentration of the release layer composition is preferably 0.1% by mass to 100% by mass, more preferably 0.5% by mass or more or 50% by mass or less, even more preferably 1.0% by mass or more or 20% by mass or less, and even more preferably 1.5% by mass or more or 10% by mass or less.

[0062] The solid content of the release layer composition includes alkylvinylpolysiloxane and alkylhydrogenpolysiloxane. The amount of the alkylvinylpolysiloxane containing a vinyl group (alkenyl group) is preferably 85.0 to 99.9 mass% based on the mass of the solid content, more preferably 90.0 mass% or more or 99.5 mass% or less, and even more preferably 92.0 mass% or more or 99.0 mass% or less.

[0063] (Film thickness of this release layer) The film thickness of the release layer is not particularly limited. If the film thickness of the release layer is thick, the influence of the substrate, for example the influence of the hardness of the substrate, tends to be difficult to be transmitted to the release surface of the release film, so it is preferably 0.01 μm or more, more preferably 0.05 μm or more, and even more preferably 0.10 μm or more. On the other hand, if the film thickness of the release layer is too thick, blocking may occur, the coating appearance may deteriorate, and so on, so it is preferably 10 μm or less, more preferably 5 μm or less, more preferably 1 μm or less, more preferably 0.5 μm or less, and especially preferably 0.25 μm or less.

[0064] <Base film> The present substrate film is not particularly limited in terms of its material as long as it has a film shape. For example, it may be made of paper, resin, metal, etc. Among these, it is preferable that it is made of resin from the viewpoint of mechanical strength and flexibility.

[0065] Examples of the resin substrate film include films formed from polymers such as polyethylene, polypropylene, polyester, polystyrene, polycarbonate, polyethersulfone, polyamide, and polyimide in the form of a film. However, the film is not limited to these. In addition, as long as it can be formed into a film, it may be a mixture of these materials (polymer blend) or a composite of the structural units (copolymer).

[0066] Among the above-mentioned films, polyester films are particularly preferred because they have excellent physical properties such as heat resistance, flatness, optical properties, and strength. The polyester film may be a single layer film or a multilayer film (laminate film) having two or more layers with different properties. The polyester film may be a non-stretched film (sheet) or a stretched film. Of these, a uniaxially or biaxially stretched film is preferred. Of these, a biaxially stretched film is more preferred from the viewpoints of balance of mechanical properties and flatness.

[0067] The polyester that is the main component resin of the polyester film may be either a homopolyester or a copolymer polyester. The main component resin means the resin that has the largest mass proportion among the resins constituting the polyester film, and is expected to account for 50 mass% or more, 75 mass% or more, 90 mass% or more, or 100 mass% of the resins constituting the polyester film.

[0068] The homopolyester is preferably one obtained by polycondensation of an aromatic dicarboxylic acid and an aliphatic glycol. Examples of the aromatic dicarboxylic acid include terephthalic acid and 2,6-naphthalenedicarboxylic acid, and examples of the aliphatic glycol include ethylene glycol, diethylene glycol, 1,4-butanediol, and 1,4-cyclohexanedimethanol, but are not limited thereto. Representative examples of homopolyester include polyethylene terephthalate (PET) and polybutylene terephthalate (PBT).

[0069] On the other hand, when the polyester is a copolymer polyester, it is preferable that the polyester is a copolymer containing 30 mol % or less of a third component. Examples of the dicarboxylic acid component of the copolymer polyester include one or more of isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, adipic acid, sebacic acid, etc., and examples of the glycol component include one or more of ethylene glycol, diethylene glycol, propylene glycol, 1,4-butanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, etc., but are not limited to these.

[0070] Among these, the main component resin of the present substrate film is preferably polyethylene terephthalate, in which 60 mol % or more, preferably 80 mol % or more, is ethylene terephthalate unit.

[0071] The present substrate film may contain particles for the main purpose of imparting easy slippage and preventing scratches in each process. When particles are contained, the type of particles contained is not particularly limited as long as it is a particle that can impart easy slippage, and specific examples include inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, and organic particles such as acrylic resin, styrene resin, urea resin, phenolic resin, epoxy resin, and benzoguanamine resin. However, the present substrate film may be used without being limited thereto. Furthermore, precipitated particles obtained by precipitating and finely dispersing a part of a metal compound such as a catalyst during the polyester manufacturing process may also be used.

[0072] On the other hand, the shape of the particles to be used is not particularly limited, and any of spherical, blocky, rod-like, flat, etc. may be used. In addition, there is no particular limit to the hardness, specific gravity, color, etc. Two or more kinds of these particles may be used in combination as necessary.

[0073] The average particle size of the particles is preferably 5 μm or less, more preferably 0.1 μm or more or 3 μm or less. By using particles with an average particle size in the above range, a suitable surface roughness can be imparted to the film, and good slipperiness and smoothness can be ensured. The average particle size of the particles can be measured as follows. The average particle size of the particles as the raw material can be measured as the average particle size (D50) determined from the volume-based particle size distribution measured by a dynamic light scattering method or the like. The average particle size of the particles contained in the substrate film can be determined by observing the surface or cross section of the substrate film using an optical microscope or a scanning electron microscope (SEM), measuring the diameters of 10 or more particles, and calculating the average value. In this case, if the cross section is elliptical, the average value of the longest and shortest diameters can be measured as the diameter of each particle.

[0074] Furthermore, the particle content in the present substrate film is preferably 5% by mass or less, more preferably 0.0003% by mass or more or 3% by mass or less. When there are no particles or only a few particles, the film has high transparency and is a good film, but the slipperiness may be insufficient, so it may be necessary to improve the slipperiness by adding particles to the coating layer. Also, when the particle content is too high, the transparency of the film may be insufficient.

[0075] <Example of this release film composition> The present release film may be configured to have the present release layer on one or both sides of the present base film, and as described below, the present base film and the present release layer may be laminated directly to each other on one or both sides of the present release film, or may be laminated via another layer.

[0076] Examples of the "other layer" include an anchor coat layer for increasing the adhesion between the substrate film and the release layer, an oligomer sealing layer for sealing the bleed (bleed, plate-out) of a compound or oligomer onto the film surface, and an antistatic layer having antistatic properties, but are not limited to these.

[0077] Specific examples of the present release film include the present base film / the present release layer, the present base film / anchor coat layer / the present release layer, the present base film / antistatic layer / the present release layer, the present base film / oligomer sealing layer / the present release layer, the antistatic layer / the present base film / antistatic layer / the present release layer, oligomer sealing layer / the present base film / oligomer sealing layer / the present release layer, the present base film / antistatic layer / oligomer sealing layer / the present release layer, the present release layer / the present base film / the present release layer, the present release layer / anchor coat layer / the present base film / anchor coat layer / the present release layer, the present release layer / antistatic layer / the present base film / antistatic layer / the present release layer, the present release layer / oligomer sealing layer / the present base film / oligomer sealing layer / the present release layer, the present release layer / oligomer sealing layer / the present base film / oligomer sealing layer / the present release layer, the present release layer / oligomer sealing layer / the present base film / oligomer sealing layer / the present release layer, the present release layer / oligomer sealing layer / antistatic layer / the present base film / antistatic layer / oligomer sealing layer / the present release layer, and the like. However, it is not limited to these.

[0078] (Anchor coat layer) Examples of the anchor coat layer include those containing polymer materials such as polyethylene, polypropylene, styrene copolymers, polyester, polyurethane, polyvinyl alcohol, polyethyleneimine, polyacrylate, polymethacrylate, and modified products thereof, but are not limited to these.

[0079] (Oligomer sealing layer) The oligomer sealing layer may contain a hydrolyzable alkoxy silicate and / or a polycondensate thereof. The hydrolyzable alkoxy silicate may be a compound having a structure represented by the following general formula (3): 1 represents a hydrocarbon group having 1 to 10 carbon atoms.

[0080] Si(OR 1 )4(3)

[0081] In formula (3), R 1 represents a hydrocarbon group having 1 to 10 carbon atoms.

[0082] The oligomer sealing layer may further contain inorganic particles, and specific examples of inorganic particles include, but are not limited to, silica, alumina, kaolin, calcium carbonate, titanium oxide, barium salts, and the like. The oligomer sealing layer may also contain, but is not limited to, an antifoaming agent, a coating improver, a thickener, an organic lubricant, an organic polymer particle, an antioxidant, an ultraviolet absorber, a foaming agent, a dye, and the like.

[0083] (Antistatic layer) From the viewpoint of imparting antistatic properties, the antistatic layer preferably contains a conductive polymer and a binder polymer. The coating liquid may contain other components as long as the gist of the present invention is not impaired.

[0084] Specifically, the conductive polymer preferably contains polythiophene represented by the following formula (4) or a derivative (I) thereof.

[0085] TIFF2025020246000002.tif33170

[0086] In the above formula (4), R1 and R2 each independently represent a hydrogen atom, an aliphatic hydrocarbon group having 1 to 12 carbon atoms, an alicyclic hydrocarbon group, or an aromatic hydrocarbon group, such as a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a cyclohexylene group, a benzene group, etc., but are not limited to these.

[0087] The above-mentioned anchor coat layer, antistatic layer, oligomer sealing layer, and other layers can be formed by either an in-line coating method in which they are formed simultaneously with the production of a film-like substrate, or an off-line coating method in which they are formed in a separate process on an already-produced substrate film. A specific example of an in-line coating method is a method in which coating is performed at any stage from melt extrusion of polyester to biaxial stretching, heat setting, and winding up. Usually, this method is performed by coating either a substantially amorphous unstretched sheet obtained by melting and quenching, a uniaxially stretched film that has been subsequently stretched in the longitudinal direction (machine direction), or a biaxially stretched film before heat setting.

[0088] <<Manufacturing method of this release film>> Next, an example of a method for producing the present release film will be described.

[0089] Generally, in a release film, measures to reduce the amount of silicone having a fluorine substituent (fluorinated silicone) used can be considered, for example, by reducing the content ratio of fluorinated silicone in the release layer, by reducing the film thickness of the release layer, etc. However, the former method impairs the light releasability, which is the original purpose, and the latter method has problems such as not being able to form the release layer uniformly and reducing the stability of the release force. In addition, by using a combination of (A) a curable silicone having a fluorine substituent (referred to as a "fluorinated curable silicone") and (B) a curable silicone not containing a fluorine substituent (also referred to as a "non-fluorinated curable silicone"), it is possible to reduce the amount of fluorinated silicone used while maintaining light release properties. However, when a solution of (A) fluorinated curable silicone and (B) non-fluorinated curable silicone is mixed and applied to a film and dried, it was confirmed that (A) fluorinated curable silicone, which has higher hydrophobicity, tends to segregate toward the surface (air interface). On the other hand, it was confirmed that the silicone crosslinking agent and catalyst used in combination do not have the same level of high hydrophobicity as (A) fluorinated curable silicone due to their molecular structure, so they do not disperse uniformly in the film, making it impossible to obtain a release layer with a good curing state, and making it impossible to mix in a large amount of (B) non-fluorinated curable silicone. Therefore, in the present invention, in forming the release layer, first, (A) a curable silicone having a fluorine substituent, (C) a silicone crosslinking agent, and (D) a curing catalyst are mixed and stirred and / or allowed to stand to react, i.e., a "pre-treatment", and then (B) a curable silicone having no fluorine substituent is mixed in to prepare the release layer composition.Even if (C1) a silicone crosslinking agent having no fluorine substituent is used as the (C) silicone crosslinking agent, it is possible to achieve the formation of a coating film that can be uniformly dispersed and is easier to peel off (lightly peelable) from the silicone adhesive.

[0090] That is, as an example of a preferred method for producing the present release film, for example, a method can be mentioned in which (A) fluorinated curable silicone, (C) silicone crosslinking agent, and (D) curing catalyst are mixed, followed by stirring and / or standing to carry out a "pre-treatment", and then the pre-treatment composition obtained in the pre-treatment is mixed with (B) non-fluorinated curable silicone to prepare the present release layer composition, and this release layer composition is applied to at least one side of the present base film to produce the present release film. However, the present release film is not limited to this production method.

[0091] After mixing (A) the fluorinated curable silicone, (C) the silicone crosslinker, and (D) the curing catalyst, a "pre-treatment" is carried out by stirring and / or leaving the mixture to stand for a short period of time, allowing the crosslinking reaction (also referred to as "pre-crosslinking") to proceed in the mixture at room temperature. In this case, the "stirring and / or leaving to stand", i.e., "pre-treatment", may be performed by any other means as long as it allows the crosslinking reaction to proceed, and the time is preferably 10 seconds or more, more preferably 1 minute or more, of which 3 minutes or more, of which 5 minutes or more, and of which 15 minutes or more is particularly preferred. There is no particular upper limit to the pre-treatment time. From the viewpoint of solvent evaporation and workability, it is preferably within 1 week, more preferably within 3 days, and particularly preferably within 1 day. If the crosslinking reaction proceeds too far, the liquid may become cloudy or gel depending on the type of material. Therefore, it is preferable to add (or supplement) a reaction control (inhibitor) agent (such as an acetylene alcohol derivative) after a predetermined pre-crosslinking time has elapsed. The reaction control agent may be added to the non-fluorinated curable silicone (or its blended liquid) described below.

[0092] As the (C) silicone crosslinking agent, as described above, it is preferable to use a silicone crosslinking agent that does not contain a fluorine substituent.

[0093] It is preferable to mix the pretreatment composition obtained in the above pretreatment with the non-fluorinated curable silicone (B), and then dilute with a solvent as necessary to prepare the release layer composition. The solvent for dilution may be a polar solvent or a non-polar solvent, and two or more of the above solvents may be mixed together. Examples of the polar solvent include alcohols such as ethanol and (iso)propyl alcohol, esters such as methyl acetate, ethyl acetate, (iso)propyl acetate, (iso)butyl acetate, (iso)pentyl acetate, ethyl lactate, and ethyl benzoate, ketones such as methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, diacetone alcohol, and diisobutyl ketone, glycols such as ethylene glycol, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether acetate, and propylene glycol monomethyl ether, N-methyl-2-pyrrolidone, N,N-dimethylformamide, tetrahydrofuran, and acetonitrile, but are not limited thereto. Examples of the non-polar solvent include aromatic hydrocarbons such as benzene, toluene, and xylene, aliphatic hydrocarbons such as hexane, heptane, and octane, hydrocarbons having a branched structure such as isohexane, isooctane, and isononane, alicyclic hydrocarbons such as cyclohexane, cycloheptane, and cyclooctane, ethers such as diisopropyl ether, and dioxane. Examples of the fluorine-containing solvent include hydrofluoroethers, metaxylene hexafluoride, and tridecafluorooctane. However, the solvent is not limited to these.

[0094] The method of applying the release layer composition to the substrate film may be, for example, a coating technique such as that shown in "Coating Method" (by Yuji Harazaki, Maki Shoten, published in 1979). For example, examples of coating heads include air doctor coaters, blade coaters, rod coaters, knife coaters, squeeze coaters, impregnation coaters, reverse roll coaters, transfer roll coaters, gravure coaters, kiss roll coaters, cast coaters, spray coaters, curtain coaters, calendar coaters, and extrusion coaters. However, the present invention is not limited to these.

[0095] (Method of forming other layers) As described above, the present release film can be formed by forming, as necessary, "other layers" such as an anchor coat layer, an antistatic layer, an oligomer sealing layer, etc. on one or both sides of a base film, and then applying and curing a release layer composition. When forming "other layers" in this manner, "other layers" such as an anchor coat layer, an antistatic layer, an oligomer sealing layer, etc. are formed, as necessary, on at least one side of the base film unwound from a roll, and then a release layer composition is applied and cured to form a release layer.

[0096] <Physical properties of this release film> The release film may have the following physical properties:

[0097] (Normal peel strength) The normal peel strength of the release layer is preferably 75 mN / cm or less, more preferably 60 mN / cm or less, even more preferably 50 mN / cm or less, and even more preferably 40 mN / cm or less. The lower the normal peel strength, the less force is required to peel off the silicone adhesive, and defects such as peel failure and deformation of the adhesive layer in the production process can be suppressed. In addition, by using a release film with excellent light peeling properties, it is possible to prevent the phenomenon in which the release film on the unintended side is peeled off in a double-sided adhesive tape having release films on both sides of the adhesive sheet. On the other hand, there is no particular restriction on the lower limit, but in terms of long-term storage of a laminate in which a release film and a pressure-sensitive adhesive are laminated, the lower limit is preferably 1 mN / cm or more. The normal peel strength can be measured by laminating a 5 cm wide adhesive tape "polyimide tape with silicone adhesive No. 5413 (manufactured by 3M)" and using a peel tester at room temperature, i.e., 23°C, at 180° peeling and 0.3 m / min.

[0098] (heat peel strength) The heat peel strength of the release layer is preferably 100 mN / cm or less, more preferably 80 mN / cm or less, and even more preferably 60 mN / cm or less. The heat peeling force is thought to be correlated with the reactive groups (such as hydrogen silane groups (Si-H groups)) remaining on the surface of the release layer after it has hardened and formed on the film. The closer the value is to the normal peeling force, the fewer the amount of reactive groups remaining on the surface. The heat peel strength is measured by attaching an adhesive tape "polyimide tape with silicone adhesive No. 5413 (manufactured by 3M)" and cutting it to a size of 50 mm x 300 mm, heat treating it in a hot air oven at 100°C for 1 hour, then removing the sample and measuring the peel strength after leaving it at room temperature for 1 hour. The peel strength can be measured, for example, by using Shimadzu Corporation's "EZ Graph" and performing 180° peeling at a tensile speed of 0.3 (m / min).

[0099] (Residual adhesion rate) The residual adhesion rate of the release layer is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more. By satisfying the above range, transfer of the components of the release layer from the surface to the surface of the opposing adherend to be bonded is reduced. The residual adhesion rate is an index for checking the transfer of the release agent, and is usually expressed as the ratio of the adhesive strength after sticking an adhesive tape to a release agent-coated surface and peeling it off, at room temperature, i.e., 23°C, divided by the initial adhesive strength (JIS Z 0109:2015).

[0100] <<This film laminate>> An example of a film laminate according to an embodiment of the present invention (referred to as "the present film laminate") is one in which the above-mentioned present release film is bonded to a "laminate film having a functional layer" via a silicone adhesive layer.

[0101] <Laminated film (1)> An example of the "laminated film having a functional layer" is a laminated film having a crosslinked resin layer, i.e., a layer having a structure formed by crosslinking a resin, on at least one side of a base film (referred to as "laminated film (1)").

[0102] In this case, the crosslinked resin layer may be, for example, a layer formed from a crosslinked resin layer composition containing a conductive polymer and a binder polymer, and optionally a crosslinking agent and particles.

[0103] (Conductive Polymer) The conductive polymer preferably contains a composition consisting of a polythiophene and a polyanion, or a composition consisting of the above-mentioned polythiophene derivative and a polyanion.

[0104] The polyanion refers to an "acidic polymer in a free acid state", and is preferably a polymeric carboxylic acid, or a polymeric sulfonic acid, polyvinyl sulfonic acid, or the like. Specific examples of polymeric carboxylic acids include polyacrylic acid, polymethacrylic acid, and polymaleic acid. Specific examples of polymeric sulfonic acids include polystyrene sulfonic acid. Among them, polystyrene sulfonic acid is most preferable in terms of electrical conductivity. In addition, the free acid may be in the form of a salt in which a part of the free acid is neutralized. By using these polyanions during polymerization, it is easy to disperse or make aqueous-soluble polythiophene-based compounds, which are originally insoluble in water, and it is considered that the function as an acid also functions as a doping agent for polythiophene-based compounds.

[0105] In addition, the polymeric carboxylic acid or polymeric sulfonic acid can be used in a form copolymerized with other copolymerizable monomers, such as acrylic acid esters, methacrylic acid esters, styrene, etc. The molecular weight of the polymeric carboxylic acid or polymeric sulfonic acid used as the polyanion is not particularly limited, but in terms of the stability and conductivity of the coating agent, the mass average molecular weight is preferably 1000 to 1000000, more preferably 5000 to 150000. It may contain alkali salts such as lithium salts and sodium salts, ammonium salts, etc., as long as the characteristics of the present invention are not impaired. In the case of neutralized salts, it has been found that polystyrene sulfonic acid and ammonium salts, which function as very strong acids, shift the equilibrium to the acidic side due to the progress of the equilibrium reaction after neutralization, and this is thought to act as a dopant.

[0106] The polyanion is preferably present in excess of the polythiophene or polythiophene derivative in terms of the solid content mass ratio in terms of electrical conductivity, and the polyanion is preferably present in an amount of 1 to 5 parts by mass, more preferably 1 to 3 parts by mass, per part by mass of polythiophene or polythiophene derivative. Regarding the composition consisting of the polythiophene or polythiophene derivative and the polyanion, for example, JP-A-6-295016, JP-A-7-292081, JP-A-1-313521, JP-A-2000-6324, European Patent EP602731, US Patent US5391472, etc., there are examples described, but other methods may also be used. As an example, 3,4-ethylenedioxythiophene is obtained using an alkali metal salt of 3,4-dihydroxythiophene-2,5-dicarboxy ester as a starting material, and then potassium peroxodisulfate, iron sulfate, and the previously obtained 3,4-ethylenedioxythiophene are introduced into an aqueous polystyrene sulfonic acid solution and reacted to obtain a composition in which a polythiophene such as poly(3,4-ethylenedioxythiophene) is complexed with a polyanion such as polystyrene sulfonic acid.

[0107] For example, there is an example described in "Latest Trends in Conductive Polymer Technology" (published by Toray Research Center, Inc., first printing June 1, 1999).

[0108] (Binder polymer) The binder polymer constituting the crosslinked resin layer composition is defined as a polymer compound having a number average molecular weight (Mn) of 1000 or more as measured by gel permeation chromatography (GPC) in accordance with the Polymer Compound Safety Evaluation Flow Scheme (November 1985, sponsored by the Chemical Substances Council), and having film-forming properties.

[0109] The binder polymer constituting the crosslinked resin layer composition may be a thermosetting resin or a thermoplastic resin as long as it is compatible with or can be mixed and dispersed in the ionic polymer. For example, polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyimides such as polyimide and polyamideimide; polyamides such as polyamide 6, polyamide 6,6, polyamide 12, and polyamide 11; fluororesins such as polyvinylidene fluoride, polyvinyl fluoride, polytetrafluoroethylene, ethylene tetrafluoroethylene copolymer, and polychlorotrifluoroethylene; vinyl resins such as polyvinyl alcohol, polyvinyl ether, polyvinyl butyral, polyvinyl acetate, and polyvinyl chloride; epoxy resins; oxetane resins; xylene resins; aramid resins; polyimide silicones; polyurethanes; polyureas; melamine resins; phenolic resins; polyethers; acrylic resins, and copolymers thereof. These may be used alone or in combination of two or more. However, the present invention is not limited to these.

[0110] The binder polymer may be dissolved in an organic solvent as a raw material, or may be dissolved in an aqueous solution by adding a functional group such as a hydroxyl group, a sulfo group, or a carboxy group, or may be dispersed in water by using a surfactant in combination. In addition, the binder polymer may be used in combination with a crosslinking agent, a curing agent such as a polymerization initiator, a polymerization accelerator, a solvent, a viscosity modifier, etc., as necessary.

[0111] Among the binder polymers, from the viewpoint of adhesion to the release layer, it is preferable to use at least one selected from polyester resins, acrylic resins, urethane resins, and vinyl resins.

[0112] The content of the binder polymer in the crosslinked resin layer composition is preferably 5 to 90% by mass, more preferably 10 to 70% by mass, and further preferably 10 to 60% by mass, in terms of solid content mass ratio. When the content of the binder polymer is within the above range, the strength of the obtained crosslinked resin layer and the adhesion to the release layer can be sufficiently obtained.

[0113] (Crosslinking agent) The crosslinked resin layer composition may contain a crosslinking agent, if necessary. The crosslinking agent can improve the cohesiveness, surface hardness, scratch resistance, solvent resistance, water resistance, etc. of the crosslinked resin layer mainly by crosslinking reactions with functional groups contained in other resins or compounds, or by self-crosslinking.

[0114] Any type of crosslinking agent can be used. For example, melamine compounds, guanamine-based, alkylamide-based, and polyamide-based compounds, glyoxal-based, carbodiimide compounds, epoxy compounds, oxazoline compounds, aziridine compounds, isocyanate compounds, silane coupling agents, dialcohol aluminate-based coupling agents, dialdehyde compounds, zircoaluminate-based coupling agents, peroxides, heat- or light-reactive vinyl compounds, photosensitive resins, and the like are preferably used. Among them, from the viewpoint of synergistically obtaining good adhesion to the release layer, it is preferable to use melamine compounds, epoxy compound crosslinking agents, and silane coupling agents. These crosslinking agents also include polymer-type crosslinking reactive compounds having reactive groups on other polymer skeletons, and in the present invention, these crosslinking agents may be used alone or in combination of two or more.

[0115] The content of the crosslinking agent in the crosslinked resin layer composition is preferably 1 to 90% by mass, more preferably 3 to 50% by mass, and further preferably 5 to 40% by mass, in terms of solid content mass ratio. If the ratio of the crosslinking agent is within the above range, sufficient adhesion to the release layer can be obtained due to the synergistic effect with the binder polymer.

[0116] (particle) For the purpose of improving the adhesion and slippage of the crosslinked resin layer, the crosslinked resin layer may contain particles. There is no particular restriction on the average particle size of the particles. For example, when used for optical purposes, from the viewpoint of film transparency, the average particle size is preferably 1.0 μm or less, more preferably 0.5 μm or less, and even more preferably 0.2 μm or less. Also, from the viewpoint of improving the adhesion and slip properties of the crosslinked resin layer, the average particle size is preferably 0.01 μm or more. Specific examples of particles include inactive inorganic particles such as silica, alumina, calcium carbonate, and titanium dioxide; fine particles obtained from polystyrene resins, polyacrylic resins, and polyvinyl resins; and organic particles such as crosslinked particles of these resins.

[0117] The average particle size of the particles can be measured as follows. The average particle size of the particles as the raw material can be measured as the average particle size (D50) determined from the volume-based particle size distribution measured by a dynamic light scattering method or the like. The average particle size of the particles contained in the crosslinked resin layer can be determined by observing the surface or cross section of the crosslinked resin layer using an optical microscope or a scanning electron microscope (SEM), measuring the diameters of 10 or more particles, and calculating the average value. In this case, if the cross section is elliptical, the average value of the longest diameter and the shortest diameter can be measured as the diameter of each particle.

[0118] (others) The crosslinked resin layer may contain, as necessary, a surfactant, an antifoaming agent, a coatability improving agent, a release agent, a thickener, an organic lubricant, an antistatic agent, a conductive agent, an ultraviolet ray or other light absorber, an antioxidant, a foaming agent, a dye, a pigment, and the like.

[0119] The components in the crosslinked resin layer can be analyzed by, for example, TOF-SIMS, ESCA, fluorescent X-ray analysis, or the like.

[0120] (Method of forming crosslinked resin layer) The crosslinked resin layer may be formed by in-line coating, which treats the surface of the polyester film during the stretching process, or off-line coating, which applies the layer outside the system to a film that has already been produced. In-line coating is preferably used because it is possible to apply the layer simultaneously with film production, making production inexpensive, and the thickness of the crosslinked resin layer can be changed by changing the stretch ratio.

[0121] Although the in-line coating is not limited to the following, for example, in the case of sequential biaxial stretching, a coating treatment can be carried out especially before transverse stretching after the completion of longitudinal stretching. When a crosslinked resin layer is provided on a polyester film by in-line coating, coating can be performed simultaneously with film formation, and the crosslinked resin layer can be treated at a high temperature, so that a film suitable as a polyester film can be produced.

[0122] When the crosslinked resin layer is provided by in-line coating, it is preferable to coat the coating liquid on the polyester film as an aqueous solution or aqueous dispersion of the crosslinked resin layer composition containing the above-mentioned series of compounds. In addition, the coating liquid may contain a small amount of organic solvent for the purpose of improving dispersibility in water, improving film-forming properties, etc., within a range that does not impair the gist of the present invention. The organic solvent may be used alone or in combination of two or more kinds.

[0123] The content of the organic solvent in the coating liquid is preferably 10% by mass or less, more preferably 5% by mass or less.Specific examples of the organic solvent include aliphatic or alicyclic alcohols such as n-butyl alcohol, n-propyl alcohol, isopropyl alcohol, ethyl alcohol, and methyl alcohol, glycols such as propylene glycol, ethylene glycol, and diethylene glycol, glycol derivatives such as n-butyl cellosolve, ethyl cellosolve, methyl cellosolve, and propylene glycol monomethyl ether, ethers such as dioxane and tetrahydrofuran, esters such as ethyl acetate and amyl acetate, ketones such as methyl ethyl ketone and acetone, and amides such as N-methylpyrrolidone.

[0124] Regardless of whether off-line coating or in-line coating is used, heat treatment and irradiation with active energy rays such as ultraviolet rays may be used in combination, if necessary.

[0125] Examples of a method for forming the crosslinked resin layer include gravure coating, reverse roll coating, die coating, air doctor coating, blade coating, rod coating, bar coating, curtain coating, knife coating, transfer roll coating, squeeze coating, curtain coating, impregnation coating, kiss coating, spray coating, calendar coating, and extrusion coating.

[0126] (Thickness of cross-linked resin layer) From the viewpoint of exhibiting various functionalities when viewed as a final coating, the thickness of the crosslinked resin layer is preferably 0.01 μm to 3 μm, more preferably 0.02 μm or more or 1 μm or less, and even more preferably 0.03 μm or more or 0.3 μm or less. The coating amount of the coating solution containing the crosslinked resin layer composition is usually 0.01 to 3 g / m 2 , preferably 0.01 to 1 g / m 2 , and more preferably 0.01 to 0.3 g / m 2 0.01g / m 2If the thickness is more than 3 g / m, sufficient performance can be obtained in terms of adhesion to the release layer (easy adhesion performance) and antistatic performance. 2 If it is equal to or less than this, the crosslinked resin layer has good appearance and transparency, and there is no risk of film blocking or reduced productivity due to a decrease in line speed. In the present invention, the coating amount can be calculated from the liquid mass per coating time (before drying), the non-volatile content concentration of the coating liquid, the coating width, the stretching ratio, the line speed, and the like.

[0127] <Laminated film (2)> An example of the "laminated film having a functional layer" is a release film having an "other release layer" on one side of the base film (referred to as "laminated film (2)").

[0128] An example of the "other release layer" is one having, in order, a first layer formed from a silicone composition containing, as a main component, (B) a curable silicone that does not contain a fluorine substituent, and a second layer containing a component having a fluorine substituent.

[0129] Another example of the "other release layer" is (A) a layer formed from a silicone composition containing, as a main component, a curable silicone containing a fluorine substituent.

[0130] Furthermore, another example of the "other release layer" is (B) a layer formed from a silicone composition containing, as a main component, a curable silicone that does not contain a fluorine substituent.

[0131] The above-mentioned "main component" means the component that occupies the largest mass proportion among the constituent components.

[0132] <Applications of this film laminate> The present film laminate is preferably used for bonding on-vehicle members, since it can use a silicone pressure-sensitive adhesive having good durability and transparency.

[0133] <Method of using the release film and the film laminate> Since the present release film has excellent releasability for silicone pressure-sensitive adhesives, it can be used as a light release film for silicone pressure-sensitive adhesives as follows. That is, in a film laminate having a configuration in which this release film (referred to as a "light release film") is laminated on one side of a silicone pressure-sensitive adhesive layer made of a silicone pressure-sensitive adhesive, and a release film (referred to as a "heavy release film") having a higher peel strength than the release film is laminated on the other side of the silicone pressure-sensitive adhesive layer, the light release film can be peeled off, the exposed surface of the silicone pressure-sensitive adhesive layer can be attached to an "adherend", the silicone pressure-sensitive adhesive layer can be cured, and the heavy release film can be peeled off for use. However, the use is not limited to this method.

[0134] Examples of the adherend include various types of process paper, inserts, and optical members. The optical member may be a polarizing plate or a touch sensor. In addition, by taking advantage of the heat resistance, cold resistance, weather resistance and high transparency of the silicone adhesive itself, it can also be used for in-vehicle applications such as touch panels installed in automobiles.

[0135] (Silicone adhesive) The silicone adhesive may be an adhesive containing silicone as a main component resin. The "main component resin" means the resin that has the largest content (mass) among the resins that make up the pressure-sensitive adhesive. Examples of the silicone adhesive include addition reaction type, peroxide curing type, and condensation reaction type silicone adhesives. Among them, addition reaction type silicone adhesives are preferably used from the viewpoint of being curable at low temperature in a short time. Note that these addition reaction type silicone adhesives are cured when the adhesive layer is formed on the support. When an addition reaction type silicone pressure-sensitive adhesive is used as the silicone pressure-sensitive adhesive, the silicone pressure-sensitive adhesive may contain a catalyst such as a platinum catalyst. For example, the addition reaction type silicone pressure-sensitive adhesive can be prepared by, if necessary, diluting a silicone resin solution with a solvent such as toluene, adding a catalyst such as a platinum catalyst, stirring until homogeneous, applying the solution onto a support, and curing the solution at 100 to 130°C for 1 to 5 minutes. If necessary, a crosslinking agent or an additive for controlling adhesive strength may be added to the addition reaction type silicone adhesive, or the support may be subjected to a primer treatment before the adhesive layer is formed.

[0136] Commercially available silicone resins for use in the addition reaction type silicone pressure sensitive adhesive include SD4580PSA, SD4584PSA, SD4585PSA, SD4587LPSA, SD4560PSA, SD4570PSA, SD4600FCPSA, SD4593PSA, DC7651ADHESIVE, DC7652ADHESIVE, LTC-755, LTC-310 (all manufactured by Dow Corning Toray Co., Ltd.), KR-3700, KR-3701, X-40-3237-1, X-40-3240, X X-40-3291-1, X-40-3229, X-40-3323, X-40-3306, X-40-3270-1 (all manufactured by Shin-Etsu Chemical Co., Ltd.), AS-PSA001, AS-PSA002, AS-PSA003, AS-PSA004, AS-PSA005, AS-PSA012, AS-PSA014, PSA-7465 (all manufactured by Arakawa Chemical Industries Co., Ltd.), TSR1512, TSR1516, TSR1521 (all manufactured by Momentive Performance Materials, Inc.), etc. can be mentioned, however, not limited to these.

[0137] (Polarizing plate) The polarizing plate may be made of any material and have any structure. For example, a polarizing plate of this type is widely used in which a TAC (triacetyl cellulose) film is laminated as a protective film on a stretched polyvinyl alcohol film using iodine as an orientation dye. The polarizing plate may have a layer structure on the surface thereof, which layer has a hard coat having substantially no retardation, antiglare, low reflection, antistatic function, etc.

[0138] (Touch Sensor) The touch sensor is a component that detects the touched point when a user touches an image displayed on a screen with a finger or a touch pen, and depending on the sensor technology, examples include a capacitive type, a resistive film type, and a surface wave type using infrared rays or ultrasound. Touch sensors are generally installed in display devices such as liquid crystal display panels and organic electroluminescence (EL) displays. Furthermore, in recent years, there has been a trend to use base films as an alternative to glass substrates, focusing on their flexibility. Touch sensor films typically include a patterned transparent conductive layer to perform the function of a sensing electrode.

[0139] <Explanation of terms, etc.> Generally, a "sheet" is defined in JIS as a thin, flat product whose thickness is small relative to its length and width, and generally, a "film" is a thin, flat product whose thickness is extremely small relative to its length and width, and whose maximum thickness is arbitrarily limited, and which is usually supplied in the form of a roll (Japanese Industrial Standards; JIS K6900). However, the boundary between a sheet and a film is unclear, and since there is no need to distinguish between the two in the present invention, in the present invention, when it is referred to as a "film", it is intended to include a "sheet", and when it is referred to as a "sheet", it is intended to include a "film".

[0140] In the present invention, when it is described as "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as the meaning of "preferably larger than X" or "preferably smaller than Y". In addition, when it is stated that the amount is "X or more" (X is any number), it also means that the amount is "preferably greater than X" unless otherwise specified, and when it is stated that the amount is "Y or less" (Y is any number), it also means that the amount is "preferably smaller than Y" unless otherwise specified. EXAMPLES

[0141] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.

[0142] <Evaluation method> (1) Normal peel strength A 5 cm wide adhesive tape, "Polyimide tape with silicone adhesive No. 5413 (manufactured by 3M)," was attached to the release surface of the sample film, and the normal peel strength was measured at room temperature (23°C) using a peel tester at 180° peeling and 0.3 m / min.

[0143] (2) Heat peeling strength An adhesive tape "polyimide tape with silicone adhesive No. 5413 (manufactured by 3M)" was attached to the release surface of the sample film, then it was cut to a size of 50 mm x 300 mm and heat-treated in a hot air oven at 100°C for 1 hour. The sample was then removed and left at room temperature (23°C) for 1 hour, after which the peel strength was measured. The peel strength was measured using Shimadzu Corporation's "EZ Graph," and 180° peeling was performed at room temperature (23° C.) under conditions of a tensile speed of 0.3 (m / min). The lower the value of the heat peel strength, the better the peeling properties can be evaluated.

[0144] (3) Residual adhesion rate (evaluation of migration of release layer) A silicone adhesive tape (3M No. 5413) was applied to the release surface of the sample film using a 2 kg rubber roller, and then cut into a 50 mm x 250 mm length to serve as a sample for measuring the residual adhesion rate. After heating for 1 hour in an oven heated to 100°C, the tape was cut into a 20 mm width and left at room temperature and humidity for 1 hour. The adhesive tape peeled off from the measurement sample was pressed onto a cleaned stainless steel plate (60 mm x 150 mm) using a rubber roller. The peel strength was measured using Shimadzu Corporation's "EZ Graph," and 180° peeling was performed at room temperature (23° C.) under conditions of a tensile speed of 0.3 (m / min). The measured peel strength of the evaluation film for residual adhesion rate and the peel strength of the reference film (a sample in which No. 5413 tape was bonded to Naflon tape instead of the sample film) were then substituted into the following formula to calculate the residual adhesion rate (%). Residual adhesion rate (%) = (peel strength of migration evaluation film / peel strength of reference film) x 100

[0145] (4) Fluorine atom concentration (atom%) in the thickness direction of the release layer Using GC-IB (Gas Cluster Ion Beam) for XPS (X-ray Photoelectron Spectroscopy), the concentration distribution (ratio) of carbon (C), oxygen (O), silicon (Si) and fluorine (F) atoms in the thickness direction of the release layer of the sample film was measured under a constant sputtering rate (sputtering condition setting).

[0146] In this case, the XPS setting conditions are as follows: Equipment: ULVAC-PHI PHI5000 VersaProbe II =Analysis conditions= X-ray intensity: AlKα / 15kV・25W Measurement range: 100μmφ Pass energy: 58.70 eV Charge correction: 284.6eV (C1s) =Sputtering conditions= Ar-GCIB 10kV, 60 minutes (3 minute intervals, 20 levels)

[0147] The obtained fluorine atom concentration distribution (vertical axis: fluorine atom concentration (atom%), horizontal axis: sputtering time (min)) was divided equally into nine parts based on the total sputtering time to determine the first measurement point (sputtering time 0 seconds, release layer surface) to the tenth measurement point (base, reaching the substrate PET film), and the fluorine atom concentration (atom%) at each measurement point was calculated. Then, the ratio (%) of the fluorine atom concentration (atom%) at the second measurement point to the fluorine atom concentration (atom%) at the first measurement point, and the ratio (%) of the average fluorine atom concentration (atom%) at the sixth to tenth measurement points to the fluorine atom concentration (atom%) at the first measurement point were calculated and shown in Table 1.

[0148] <Example 1> Solution a1 was prepared by mixing the following (A) curable silicone having a fluorine substituent, the following (C1) silicone crosslinking agent, and the following (D1) curing catalyst 1. After stirring for 1 minute, the following solution b1 ((B) curable silicone not containing a fluorine substituent + (D2) curing catalyst 2) was added so that the mass ratio (solution a1:solution b1) was 1:2, and coating solution A1 with a solid content concentration of 3.6 mass% was prepared. Then, the coating liquid A1 was applied to one side of a base film (PET film ("T100-38", thickness 38 μm) manufactured by Mitsubishi Chemical Corporation) using a No. 4 bar, and the coating liquid A1 was cured by heat treatment at 150°C for 15 seconds to obtain a release film (sample film) provided with a release layer.

[0149] (Release Layer Composition) Solution A1: (A) Curable silicone having a fluorine substituent (Toray Dow Corning Co., Ltd. "3062", 10% by weight, viscosity 10mm 2 / s) 100 parts by mass (C1) Silicone crosslinker containing no fluorine substituents (Toray Dow Corning Co., Ltd. "3062A") 0.50 parts by weight (D1) Platinum catalyst 1 (Toray Dow Corning Co., Ltd. "FS XK-3077") 0.50 parts by weight Diisopropyl ether / ethyl acetate (3:7)

[0150] Solution b1: (B) Curable silicone containing no fluorine substituents (Shin-Etsu Chemical Co., Ltd. "KS-847H", solvent-based, 30% by weight, contains crosslinker / reaction regulator, viscosity 11000 mPa·s (25°C)) 67 parts by weight (D2) Platinum catalyst 2 (“CAT-PL-50T” manufactured by Shin-Etsu Chemical Co., Ltd.) 0.67 parts by mass Diisopropyl ether / ethyl acetate (3:7)

[0151] <Example 2> to <Example 5> Release films (sample films) were obtained in the same manner as in Example 1, except that in Example 1, after the preparation of solution a1, stirring was carried out for 1 minute and the standing time was further added as shown in the table.

[0152] <Example 6> In Example 1, solution a1 was prepared to have a solid content concentration of 10% by mass, stirred for 1 minute, allowed to stand for a further 15 minutes, and then diluted with a solvent to have a solid content concentration of 3.6% by mass. A release film (sample film) was obtained in the same manner as in Example 1.

[0153] <Comparative Example 1> A release film (sample film) was obtained in the same manner as in Example 1, except that no stirring was carried out at all. Here, "no stirring was performed at all" means that "after (C1) the silicone crosslinking agent and (D1) the curing catalyst 1 were mixed to prepare solution a1, solution b2 was immediately mixed in without stirring to prepare coating solution A1."

[0154] <Comparative Example 2> A release film (sample film) was obtained in the same manner as in Example 1, except that (B) the curable silicone not containing a fluorine substituent and (D2) the curing catalyst 2 were not mixed.

[0155] <Comparative Example 3> A release film (sample film) was obtained in the same manner as in Example 2, except that (C1) the silicone crosslinking agent not containing a fluorine substituent was replaced with (C2) a crosslinking agent having a fluorine substituent (Dow Corning Toray Co., Ltd. "3062C") (0.5 parts by mass).

[0156] <Comparative Example 4> In Comparative Example 2, a release film (sample film) was obtained in the same manner as in Example 1, except that (C1) the silicone crosslinking agent not containing a fluorine substituent was replaced with (C2) a crosslinking agent having a fluorine substituent (Dow Corning Toray Co., Ltd. "3062C") (0.5 parts by mass).

[0157] <Comparative Example 5> Solution b2 was prepared by mixing 100 parts by mass of TPR6600 (manufactured by Momentive Corporation) as a curable silicone not containing fluorine substituents (containing a crosslinking agent not containing fluorine substituents) with 3 parts by mass of LC600 (manufactured by Momentive Corporation) as a curing catalyst. Solution a2 was prepared by mixing 100 parts by mass of BY24-900 (manufactured by Dow Corning Toray Co., Ltd.) as a curable silicone (including a crosslinking agent) having a fluorine substituent with 0.5 parts by mass of NC-25 (manufactured by Dow Corning Toray Co., Ltd.) as a curing catalyst. 100 parts by mass of solution a2 containing the curable silicone having a fluorine substituent was blended and mixed with 100 parts by mass of solution b2 containing the curable silicone not having a fluorine substituent, and a solvent prepared by mixing n-heptane and methyl isobutyl ketone in a 1:1 weight ratio was added to dissolve the polymer component, thereby preparing coating solution A2 with a solids concentration of 3.0 mass%. Before mixing solution a2 and solution b2, no stirring was performed. Here, "no stirring at all" means that "after preparation of solution a2, solution b2 was immediately mixed therewith without stirring to prepare coating solution A2." Then, the coating solution A2 was applied to one side of a base film (PET film ("T100-38", thickness 38 μm) manufactured by Mitsubishi Chemical Corporation) using a No. 10 bar, and the coating solution A2 was cured by heat treatment at 120°C for 120 seconds to obtain a release film (sample film) provided with a release layer.

[0158] <Comparative Example 6> Solution a2 was prepared by mixing 100 parts by mass of BY24-900 (manufactured by Dow Corning Toray Co., Ltd.) as a curable silicone (including a crosslinking agent) having a fluorine substituent with 0.5 parts by mass of NC-25 (manufactured by Dow Corning Toray Co., Ltd.) as a curing catalyst. A solvent prepared by mixing n-heptane and methyl isobutyl ketone in a weight ratio of 1:1 was added to the solution a2 to dissolve the polymer component, thereby preparing a coating solution A3 having a solid content concentration of 3.6% by mass. Then, the coating solution A3 was applied to one side of a base film (PET film ("T100-38", thickness 38 μm) manufactured by Mitsubishi Chemical Corporation) using a No. 4 bar, and the coating solution A3 was cured by heat treatment at 120°C for 120 seconds to obtain a release film (sample film) provided with a release layer.

[0159] [Table 1]

[0160] [Table 2]

[0161] <Consideration> From the above examples and the results of tests conducted by the inventors thus far, it has been found that a release layer formed on at least one side of a base film, which is formed by curing a release layer composition containing (A) a curable silicone having a fluorine substituent, (B) a curable silicone not containing a fluorine substituent, and (D) a curing catalyst, has excellent easy peelability from the silicone pressure-sensitive adhesive layer, even when the amount of fluorinated silicone used is reduced. Moreover, when a common feature of such release layers was investigated, it was found that fluorine was unevenly distributed on the surface of the release layer in the concentration distribution of fluorine atoms in the thickness direction of the release layer. More specifically, in the fluorine atomic concentration distribution (vertical axis: fluorine atomic concentration (atom%), horizontal axis: sputtering time (min)) obtained as in the above example, when the total sputtering time was divided equally into nine parts to determine the first measurement point (sputtering time 0), the second measurement point, to the tenth measurement point, it was found that the fluorine atomic concentration (atom%) at the second to tenth measurement points was 80.0% or less of the fluorine atomic concentration (atom%) at the first measurement point (sputtering time 0). Furthermore, it was found that if the average fluorine atom concentration (atom%) at the sixth to tenth measurement points was higher than the fluorine atom concentration (atom%) of 2.2% at the first measurement point (sputtering time 0), an even better effect could be achieved, that is, excellent easy peelability from the silicone adhesive layer could be obtained even if the amount of fluorinated silicone used was reduced.

[0162] On the other hand, in the above-mentioned method for forming the release layer, the following was found. When a mixed solution of (A) curable silicone having a fluorine substituent and (B) curable silicone not having a fluorine substituent was applied onto a film and dried, it was confirmed that the more hydrophobic curable silicone having a fluorine substituent (A) was more likely to segregate toward the surface (air interface). On the other hand, the silicone crosslinking agent and catalyst used in combination do not have the same level of high hydrophobicity as (A) curable silicone with fluorine substituents due to their molecular structure, and therefore they do not disperse uniformly in the film, making it impossible to obtain a release layer in a good cured state, or making it impossible to mix in a large amount of (B) curable silicone without fluorine substituents. Therefore, in the present invention, a "pretreatment" is first carried out by mixing (A) a curable silicone having a fluorine substituent, (C) a silicone crosslinking agent, and (D) a curing catalyst, and then stirring and / or leaving them to react. The pretreatment composition obtained in the pretreatment is then mixed with (B) a curable silicone having no fluorine substituent to prepare a release layer composition. It was found that even when (C1) a silicone crosslinking agent having no fluorine substituent is used, it is possible to uniformly disperse the silicone crosslinking agent, and it is also possible to form a coating film that is easier to peel off (light peelability) from a silicone pressure-sensitive adhesive. Although the details of this mechanism are unclear, it is speculated that after the preparation of the compounded liquid, a moderate amount of entanglement (pre-crosslinking) occurs in the compounded liquid as it changes over time, and that as a result, (A) curable silicone with fluorine substituents tends to exist in greater amounts on the surface (air interface) side. As a result, it is presumed that even after application to a film, the fluorine substituents remain concentrated in the vicinity of the surface of the release layer, making it possible to form a coating film with light release properties. Furthermore, it was found that by mixing in a larger amount of (B) curable silicone that does not contain fluorine substituents, it is possible to further reduce the total amount of fluorine atoms in the film during the process of forming the release layer film, thereby making it possible to efficiently express release properties.

Claims

1. A release film comprising a base film and a release layer formed on at least one side thereof by curing a release layer composition comprising (A) a curable silicone having a fluorine substituent, (B) a curable silicone not having a fluorine substituent, and (D) a curing catalyst; A release film characterized in that, in the concentration distribution of fluorine atoms in the thickness direction of the release layer, fluorine atoms are unevenly distributed on the surface of the release layer, and the fluorine atom concentration on the surface of the release layer is 39.0 atomic concentration% or more.

2. Using XPS (X-ray photoelectron spectroscopy) and GC-IB (gas cluster ion beam), the concentration distribution of fluorine atoms in the thickness direction of the release layer was measured under a constant sputtering rate. The obtained fluorine atom concentration distribution (vertical axis: fluorine atom concentration (atom%), horizontal axis: sputtering time (min)) was equally divided into nine by the total sputtering time to determine a first measurement point (sputtering time 0), a second measurement point, ..., a tenth measurement point. A release film, characterized in that the fluorine atomic concentration (atom %) at the second measurement point to the tenth measurement point is 80.0% or less of the fluorine atomic concentration (atom %) at the first measurement point (sputtering time 0).

3. Using XPS (X-ray photoelectron spectroscopy) and GC-IB (gas cluster ion beam), the concentration distribution of fluorine atoms in the thickness direction of the release layer was measured under a constant sputtering rate. The obtained fluorine atom concentration distribution (vertical axis: fluorine atom concentration (atom%), horizontal axis: sputtering time (min)) was equally divided into nine by the total sputtering time to determine a first measurement point (sputtering time 0), a second measurement point, ..., a tenth measurement point. A release film characterized in that the average fluorine atomic concentration (atom%) at the 6th to 10th measurement points is higher than the fluorine atomic concentration (atom%) at the 1st measurement point (sputtering time 0), which is 2.2% higher.

4. 4. The release film according to claim 2 or 3, which is a release film having a release layer formed by curing a release layer composition comprising (A) a curable silicone having a fluorine substituent, (B) a curable silicone not containing a fluorine substituent, and (D) a curing catalyst on at least one side of a base film.

5. The release film according to claim 1 or 4, wherein the release layer composition comprises (C) a silicone crosslinker.

6. 6. The release film according to claim 5, wherein the silicone crosslinking agent (C) is a silicone crosslinking agent that does not contain a fluorine substituent.

7. The release film according to any one of claims 1, 4, 5, and 6, wherein the mass ratio of (A) the curable silicone having a fluorine substituent to (B) the curable silicone not containing a fluorine substituent is 1:50 to 10:

1.

8. 8. The release film according to claim 1, wherein the release layer has a fluorine atom content of 500 ppm by mass or more and 800,000 ppm by mass or less.

9. 9. The release film according to claim 1, wherein the curable silicone not containing a fluorine substituent (B) is a solvent-curable silicone.

10. 10. The release film according to claim 1, wherein the release layer has a normal peel strength of 75 mN / cm or less and a residual adhesion rate of 80% or more.

11. The release film according to any one of claims 1 to 10, wherein the heat peel strength of the release layer is 100 mN / cm or less.

12. A method for producing a release film, comprising mixing (A) a curable silicone having a fluorine substituent, (C) a silicone crosslinking agent, and (D) a curing catalyst, stirring and / or allowing to stand, and then mixing with (B) a curable silicone having no fluorine substituent to prepare a release layer composition, and applying this release layer composition to at least one side of a substrate film.

13. A method for producing a release film, comprising mixing (A) a curable silicone having a fluorine substituent, (C) a silicone crosslinking agent, and (D) a curing catalyst, stirring and / or allowing to stand for 1 minute or more, and then mixing the mixture with (B) a curable silicone having no fluorine substituent to prepare a release layer composition, and applying this release layer composition to at least one side of a substrate film.

14. 14. The method for producing a release film according to claim 12 or 13, characterized in that as the silicone crosslinking agent (C), a silicone crosslinking agent not containing a fluorine substituent is used.

15. 12. A film laminate comprising a structure in which the release film according to claim 1 is bonded to a laminate film having a functional layer via a silicone pressure-sensitive adhesive layer.

16. The film laminate according to claim 15, wherein the laminate film having a functional layer is a laminate film having a crosslinked resin layer provided on at least one side of a base film.

17. The film laminate according to claim 16 , wherein the crosslinked resin layer contains a conductive polymer and a binder polymer.

18. The film laminate according to claim 15 , wherein the laminate film having a functional layer is a release film having another release layer on one side of a base film.

19. The film laminate according to claim 18, wherein the other release layer is configured to sequentially comprise a first layer formed from a silicone composition containing as a main component a curable silicone that does not contain a fluorine substituent (B), and a second layer containing a component that has a fluorine substituent.

20. The film laminate according to claim 18, wherein the another release layer is formed from a silicone composition containing, as a main component, (A) a curable silicone containing a fluorine substituent.

21. The film laminate according to claim 18, wherein the another release layer is formed from a silicone composition containing, as a main component, (B) a curable silicone containing no fluorine substituent.

22. The film laminate according to any one of claims 15 to 21, which is used for bonding on-board members.

23. 12. A film laminate comprising a release film (referred to as a "light release film") according to any one of claims 1 to 11 laminated to one side of a silicone pressure-sensitive adhesive layer made of a silicone pressure-sensitive adhesive, and a release film (referred to as a "heavy release film") having a higher peel strength than said release film laminated to the other side of the silicone pressure-sensitive adhesive layer, comprising: peeling off the light release film, attaching the exposed surface of the silicone pressure-sensitive adhesive layer to an adherend, curing the silicone pressure-sensitive adhesive layer, and peeling off the heavy release film.

24. The method for using a film laminate according to claim 23, characterized in that the adherend is an optical member.

25. The method for using the film laminate according to claim 24, wherein the optical component is a polarizing plate or a touch sensor.

26. 26. The film laminate according to claim 24, wherein the optical component is an optical component for use in a vehicle.

Citation Information

Patent Citations

  • Fluorosilicone-based release agent material

    JP2013510921A

  • Substrate-less double-sided adhesive sheet

    JP2014117866A

  • Release film for silicone adhesive

    JP2015183041A

  • Laminate film

    JP2018020442A

  • Silicone release agent composition, release sheet and release film

    JP2020100764A